Perancangan Dan Pembuatan Media Pembelajaran Berbasis Android Pada Mata Pelajaran Ilmu Pengetahuan Alamkelas Viii Di Smp Negeri 39 Padang Tahun Ajaran 2023/2024 - Maya Netra Rosa; Rini Sefriani; Popi Radyuli (Culture education and technology research (Cetera), 2024)
This research aims to determine the validity, practicality and effectiveness of making Android-based learning media applications in natural science subjects for class VIII at SMP Negeri 39 Padang for the 2023/2024 academic year. This research uses research development methods (research & development). The research subjects were 32 people. The research model used is the development research model (ADDIE), with the design of the development steps being as follows. (1) Analyze, (2) design, (3) development, (4) Implementation and (5) Evaluate. The results of the validity test by experts, the overall validator test assessment of Android-based Learning Media in Class VIII Natural Science Subjects at SMP Negeri 39 Padang was 84.64%, so the validity level can be interpreted as valid for use. The results of the overall practicality test assessment of the Android-based Learning Media in Class VIII Natural Science Subjects at SMP Negeri 39 Padang were 85.68%, so that the level of practicality can be interpreted as practical for use. The results of the overall effectiveness test assessment of the effectiveness of Android-Based Learning Media in Class VIII Natural Science Subjects at SMP Negeri 39 Padang were 87.77% so that the level of effectiveness can be interpreted as very effective in use. In conclusion, based on assessments along with expert input and the results of field trials, Android-based learning media as a learning medium has been tested for its suitability, superiority and can be used in the learning process in Class VIII Natural Science subjects at SMP Negeri 39 Padang.